(untitled) (Bangladesh Journal of Medical Microbiology, 2010)
The present study reports the prevalence of hepatitis C virus (HCV) infection among 70,200 voluntary blood donors. Out of them, 364 (0.52%) donors were anti-HCV positive of which 308(0.44%) were male and 56(0.08%) were female. As the donors were categorized by profession, highest number of voluntary donors were students (58%) followed by Business man (21%), Service holder (19 %) and house wife (2%). Most of the donors (43%) were in the age group of 18-25yrs. Among the professional groups of voluntary blood donors, percentage of anti HCV positive cases was highest in businessmen group (1.09%) followed by housewife (0.98%), service holders (0.73%) and students (0.22%). Bangladesh J Med Microbiol 2010; 03 (02): 1-3